Beweging in het plan: Focus en reikwijdte van integrale ruimtelijke plannen - Witsen, Peter Paul (A+BE | Architecture and the Built Environment, 2025)
So far, the 21st century has called for great dynamism and change, with the need for adaptation breaking from the trends of decades past. Classic growth and protection challenges in spatial planning have now been augmented by transition challenges such as biodiversity recovery, the quest for alternatives to fossil fuels and resources, climate adaptation and subsequent water management and the increasing tendency to prioritise broad-based prosperity over maximum economic growth. Each of these challenges makes significant claims on available space and has profound spatial effects, and each is set against a background of social unrest. Vast swathes of the electorate feel alienated from politics and politicians and are expressing their discontent in the voting booth. Implications for the planning field are twofold: the need to 1) increase spatial interconnection and 2) operate with great social sensitivity. The Dutch bring a long, proud tradition of spatial planning to these challenges, starting before WWII. Over this time, the fully integrated spatial plan served as a fulcrum in the spatial planning field. After all, the more topics that are addressed and considered in a spatial plan, the more links can be made, the closer the intended result comes to an optimal use of space, or so is believed. Full comprehensiveness (or ‘integrality’), however, also has its downsides, as a fully connected system is also a motionless system. The quest for integrality, then, can create paralysis, and the immediate reason for this study is the suspicion that Dutch spatial planning has too long and too blindly relied on the idea of a fully integrated spatial plan. A long, proud tradition, it seems, may blind its followers and stymie innovation. The main question of this study is: what can be the scope and focus of fully integrated spatial plans in modern-day Netherlands, and how do they relate to other spatial steering tools? By answering this main question, the study seeks to contribute to an effective and efficient spatial planning method that is firmly rooted in Dutch society and meets its current needs and requirements by examining what position the integrated spatial plan (the document) can have in spatial planning (the ongoing activity).